2017
DOI: 10.1126/science.aah4573
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-seq reveals new types of human blood dendritic cells, monocytes, and progenitors

Abstract: Dendritic cells (DCs) and monocytes play a central role in pathogen sensing, phagocytosis and antigen presentation and consist of multiple specialized subtypes. However, their identities and interrelationships are not fully understood. Using unbiased single-cell RNA sequencing (RNA-seq) of ~2400 cells, we identified six human DCs and four monocyte subtypes in human blood. Our study reveals: a new DC subset that shares properties with plasmacytoid DCs (pDCs) but potently activates T cells, thus redefining pDCs;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

137
2,310
5
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,987 publications
(2,569 citation statements)
references
References 73 publications
137
2,310
5
4
Order By: Relevance
“…(For interpretation of the references to color in this figure legend, the reader is referred to the Web version of this article.) population of pre-cDCs expressing AXL that highly expresses co-stimulatory molecules (See et al, 2017;Villani et al, 2017). Although it can be deduced from these studies that bona fide pDCs still outnumber contaminating cDCs using this gating strategy, it is not known whether the extent of pre-cDC contamination varies between males and females or whether it is affected by infection.…”
Section: Discussionmentioning
confidence: 99%
“…(For interpretation of the references to color in this figure legend, the reader is referred to the Web version of this article.) population of pre-cDCs expressing AXL that highly expresses co-stimulatory molecules (See et al, 2017;Villani et al, 2017). Although it can be deduced from these studies that bona fide pDCs still outnumber contaminating cDCs using this gating strategy, it is not known whether the extent of pre-cDC contamination varies between males and females or whether it is affected by infection.…”
Section: Discussionmentioning
confidence: 99%
“…3a-c). We determined the putative identity of the cells in these clusters by comparing their global gene expression patterns to those of published reference monocyte/dendritic cell (DC) clusters identified in blood samples of healthy individuals using scRNA-seq 6 (Fig. 3b,c; Supplementary Fig.…”
Section: Classification and Annotation Of Myeloid Cell Clusters Reveamentioning
confidence: 99%
“…In the blood, human DC include lineage-negative (LIN-) HLA-DR+CD14-CD11c-CD123+ plasmacytoid DC and LIN-HLA-DR+CD14-CD11c+ conventional DC subsets, of which the latter can be subdivided into four different DC subsets (DC1 to DC4) based on the additional markers CLEC9A, CD141, CD1c, CD16, CD36, CD32b and CD163. 23 , 28 Blood analysis of six EOC patients and four healthy donors revealed that the HLA-DR+CD14-CD11c+ DC subset was mainly composed of CD141+CLEC9A+ DC1, CD1c+CD32b+ DC2, CD1 c+CD32b-CD36+CD163+ DC3 and CD1c-CD16+ DC4 subsets ( Suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The latter was based on a publication by Villani and co-workers 23 and consisted of the following markers: the live/dead marker yellow amine reactive dye, CD11b-AF488 (clone ICRF44), CD16-PE-CF594 (clone 3G8), CD14-PE-Cy7 (clone M5E2), HLA-DR-V500 (clone L243), CD11c-BV650 (clone B-ly6), CD163-PerCP-Cy5.5 (clone GHI/61), CD123-BV605 (clone 9F5; all from BD), CD141-APC (clone AD5–14H12, Miltenyi Biotec), CLEC9A-PE (clone 8F9), CD36-APC-Cy7 (clone 5–271; both Biolegend), CD1c-BV421 (clone L161, eBioscienes) and CD32b-AF700 (clone #190723, R&D systems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation